POTENSI PENGEMBANGAN FASHION STREETWEAR MELALUI MOTIF DAUN SIMPUR PADA CRAB DI PROVINSI KEPULAUAN BANGKA BELITUNG - Janah, Nurul; Lusia, Rohil Agatha; Robakiah, Robakiah; Andini, Dwi; Pratiwi, Desti Aulia; Dalimunthe, Desy Yuliana (Jurnal Abdi Insani, 2024)
Fashion is a product that is created to represent individual needs. Teenage fashion is growing rapidly following the times, thus the phenomenon of fashion styles emerges, one of which is the streetwear style trend which was also a trend in the 90s. One of the streetwear fashion that is widely used is cardigan. The existence of Cardigan Rajut Bangka Belitug (CRAB) has its own market share, especially in terms of youth fashion. CRAB comes with a motif that raises elements of local wisdom of the Bangka Belitung Islands Province, namely the simpur leaf.  The purpose of this activity is to produce entrepreneurial products in the form of CRAB with simpur motifs as part of the local wisdom of the Bangka Belitung Islands Province in encouraging a new economy for students. The CRAB production process uses a product feasibility test questionnaire and economic analysis. Based on the questionnaire, the results showed that there were 111 respondents. According to respondents, the CRAB product business has the opportunity to be produced and can be accepted quite well by potential consumers by 97.3%. In addition, the CRAB product business is quite promising with the results of economic analysis obtained profits that reach> 5.5 million within 3 months. So that this business is feasible to develop based on the feasibility test and economic analysis used